Comparative Study of the Silk Fiber Structure and Properties before and after the Tensional Twisting Treatment (Journal of Fiber Bioengineering and Informatics, 2018)
The production of the silk textile products with super softness and high suspension has become one of the hot and difficult topics in textile researches. To endow the silk fiber with improved softness, tensional drawing under different conditions was used to regulate the fiber structure and reduce the fiber initial modulus. The silk fiber structural and mechanical properties were tested before and after the tensional twisting treatments under wet and dry conditions respectively. The results showed that unlike the dry drafted twisting treatment, the pre-wet tensional twisting treatment induced more uniform helical structural formation with lower crystal destruction and molecule rupture than the dry one; though the breaking force decreased, the silk softness and breaking elongation were both improved after the pre-wet twisting treatment.